Penerapan Algoritma K-Means Dalam Metode Clustering Untuk Peminatan Jurusan Bagi Siswa Swasta Pelita Raya Kota Jambi - Firza, Firza; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2020)
This research is aimed to decide major for students of SMK Swasta Pelita Raya Jambi. The interest of major is implemented when students are in the tenth grade and will move to eleventh grade. The process of major determination will be occurred repeatedly every year. This research will conduct Clustering by using the data of students of SMK Swasta Pelita Raya Jambi and utilize the science of mining data, Algorithm K-Means Clustering. Algorithm K-Means Clustering in this research is limited applying with using the mining tools data, Rapid Miner Studio. Clustering is the group of record, observation, or case in the similar object classes. The result of algorithm K-Means Means in this research produces a solution or a reference for dividing apprenticeship place that is suitable for interest and talent of students in the eleventh grade of Multimedia and Accounting.